A study on factors that influence organizational commitment of Generation Y in Matrix Concepts Holding Berhad / Mohd Syamil Mohd Nor and Nurul Nasirah No’man - Mohd Nor, Mohd Syamil; No’man, Nurul Nasirah (Faculty of Business and Management, 2016)
Recently, the Malaysian workforce is actively expanding day-by-day, generation-by generation. Nowadays, most employers are getting choosy in selecting the people who they would want to employ, as there are certain characteristics that they would look for in an employee. One of the features is organizational commitment. As the economic condition fluctuates so fast from time to time, it is not easy to found out the reason behind for a person to stay with an organization for a long period. The management of philosophers regarding the factors that would affect for an organizational commitment created a lot of theories. For this research, four factors have been identified from research done previously by other researchers, which are rewards, freedom, procedural justice and organization support. These four factors might or might not deeply affect the organizational commitment. From the research conducted to determine the organizational commitment level for this generation, it was found that Generation Y organizational commitment was affected by few significant factors. The data obtained was analysed using Statistical Package for Social Science (SPSS) version 20 and conclusions and recommendations were made based on the findings obtained.